OPTIMIZING TOURISM PROMOTION THROUGH THE USE OF CULTURAL HERITAGE - Iswanto, Dedy; Istiqlal, Istiqlal; Irsyad, Ziqrurrahman (PT. Sangadji Media Publishing, 2024)
This study aims to explore the optimization of tourism promotion through the utilization of cultural heritage by using the Systematic Literature Review (SLR) approach. The study was conducted by selecting literature from academic databases such as Scopus, DOAJ, and Google Scholar, using keywords such as “cultural heritage,” “tourism marketing strategy,” “cultural commodification,” and “smart technology” within the time span of 2014-2024. The results showed that although the integration of cultural heritage in tourism marketing strategies successfully increased destination attractiveness and visitor engagement, challenges such as cultural commodification, overtourism, and disagreements between stakeholders still need to be addressed. A balance between cultural conservation and tourism development is a key element in an effective strategy, where the preservation of local cultural identity must be considered. In addition, the use of smart technology in the promotion of local culture is proven to attract tourists, but there is a gap in understanding the impact of social media and other technologies on destination image. Therefore, future research is recommended to explore more deeply the factors that influence the success of heritage-based tourism marketing strategies and how technology can be effectively integrated in such contexts.